2021
DOI: 10.1111/ele.13785
|View full text |Cite
|
Sign up to set email alerts
|

The deep sea is a hot spot of fish body shape evolution

Abstract: Deep‐sea fishes have long captured our imagination with striking adaptations to life in the mysterious abyss, raising the possibility that this cold, dark ocean region may be a key hub for physiological and functional diversification. We explore this idea through an analysis of body shape evolution across ocean depth zones in over 3000 species of marine teleost fishes. We find that the deep ocean contains twice the body shape disparity of shallow waters, driven by elevated rates of evolution in traits associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 60 publications
(78 reference statements)
6
38
2
Order By: Relevance
“…3 ). However, previous studies have found significant but small effects of major habitat transitions on fish body shape diversification ( 63 , 64 ) that contrast with the significant and stronger results from our phylogenetic MANOVA, suggesting that feeding mode has a relatively strong influence on body shape and its evolution when compared with the effects of other ecological traits.…”
Section: Discussioncontrasting
confidence: 99%
“…3 ). However, previous studies have found significant but small effects of major habitat transitions on fish body shape diversification ( 63 , 64 ) that contrast with the significant and stronger results from our phylogenetic MANOVA, suggesting that feeding mode has a relatively strong influence on body shape and its evolution when compared with the effects of other ecological traits.…”
Section: Discussioncontrasting
confidence: 99%
“…Affinity to feeding habitat was included to define whether species feed at or near the bottom or in the pelagic, distinguishing them as demersal, pelagic, bathypelagic or benthopelagic. The shape of the body and aspect ratio of the caudal fin can inform about fish lifestyle and relate to functions such as mobility, feeding strategy, and habitat use (Friedman et al, 2020; Martinez et al, 2021). Body shape is herein described as eel‐like, fusiform, elongated, flat, and short and/or deep, whereas aspect‐ratio is a measure of the fin shape (Aspect ratio = h 2 /s; where h is height of the caudal fin, and s is surface area of the fin) (Pauly, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…To adapt to changeable environments, fish modify their morphology and physiology, and the phenotypic plasticity results in morphological divergence which may, in some instances, be involved in response to different environmental conditions 31 . Our study revealed the phenotypic divergence of Eleutheronema species among diverse populations, characterized mainly by the depth of caudal peduncle and length of caudal peduncle, indicating the evolution in the caudal peduncle which is associated with swimming behaviors in deeper waters 32 . The caudal fin was also among the variables with high loadings on the PC1, suggesting evolution in the caudal area, likely associated with the consequence of phenotypic plasticity in response to hydrological conditions.…”
Section: Resultsmentioning
confidence: 74%